2010
DOI: 10.1007/s10549-010-0807-1
|View full text |Cite
|
Sign up to set email alerts
|

NAT2 polymorphisms combining with smoking associated with breast cancer susceptibility: a meta-analysis

Abstract: To derive a more precise estimation of the relationship between the slow or rapid acetylation resulting from N-acetyltransferase 2 (NAT2) polymorphisms and breast cancer risk, a meta-analysis was performed. PubMed, Medline, Embase, and Web of Science were searched. Crude odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess strength of association. The pooled ORs were performed for slow versus rapid acetylation genotypes. A total of 26 studies including 9,215 cases and 10,443 controls were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…More recent systematic reviews with meta-analysis (Zhang et al, 2010b) and individual studies (Zhang et al, 2010a) suggest that in the long run a history of smoking in women with a polymorphism of the N-acetyltransferase 2 gene can contribute to susceptibility to cancer. On the other hand, in our university there was an unpublished study by Marian et al (2011) with solid evidence showing that in Mexican women the polymorphism of the FGFR2 gene mediates the increased risk of cancer produced by alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…More recent systematic reviews with meta-analysis (Zhang et al, 2010b) and individual studies (Zhang et al, 2010a) suggest that in the long run a history of smoking in women with a polymorphism of the N-acetyltransferase 2 gene can contribute to susceptibility to cancer. On the other hand, in our university there was an unpublished study by Marian et al (2011) with solid evidence showing that in Mexican women the polymorphism of the FGFR2 gene mediates the increased risk of cancer produced by alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis based on 37 studies including 15,260 breast cancer and 20,411 controls suggested that the MTHFR 677 T allele was a low-penetrant risk factor for developing breast cancer [35]. A meta-analysis of 26 studies including 9,215 breast cancer and 10,443 controls suggested that there was overall lack of association between N-acetyltransferase 2 (NAT2) genotypes and breast cancer risk, however, NAT2 polymorphisms when combining with heavy smoking history may contribute to breast cancer susceptibility [36]. A metaanalysis of 17 studies including 12,019 breast cancer and 10,747 controls found that ERCC2 312Asn allele may have a protective effect for breast cancer development in Asians [37].…”
Section: Discussionmentioning
confidence: 99%
“…Among NAT2 fast acetylators, subjects with a history of more than 20 pack-years were nearly two times as likely (OR: 1.93, 95%CI: 1.01–3.69) to develop breast cancer as compared to individuals with a history of less than 20 pack-years; however, no association was detected among NAT2 slow acetylators. Another recent meta-analysis [47] further suggested that NAT2 polymorphisms contribute to the risk of breast cancer when smoking history is taken into account. NAT1 genetic polymorphisms were also considered to be sensitive to smoking history in the etiology of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Combining those results, the association between passive smoking and incidence of breast cancer was not statistically significant (RR = 1.11, 95%CI: [0.55, 2.24], P = 0.78). The possible explanation was that the genetic factor may impact the effect of tobacco smoking on breast cancer [47]–[49]. In the subgroup analysis of postmenopausal women, although Hanaoka et al [12] found that passive smoking may decrease the incidence of breast cancer (RR = 0.6, 95%CI: [0.4, 1.0]), this study did not support this point by combining 4 studies (RR = 1.01, 95%CI: [0.85, 1.20], P = 0.90).…”
Section: Discussionmentioning
confidence: 99%